Kindergarten educators attitudes towards the use of educational film in kindergarten (Field study on a sample of Kindergarten educators in the Jableh area) - Ahmad, Mutieah; Mobied, Mohanad; Abbas, Zaen ALAbeden (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This current study aimes at investigating the kindergarten educators attitudes towards the use of the education film in kindergarten, the study was carried out on a sample of (40) kindergarten educators in Jableh which is a city of Lattakia province, the kindergarten educators comes from 7 kindergartens: (five of which are private and two are government). To achieve the goal of the study questionnaire of attitudes was given to the kindergarten educators. The researcher then collected the data and analyzed it. The study concluded the following conclusions: There are no significant differences at (%0,05) among the means of answers scores kindergarten educators On the questionnaire of the attitudes that can be attributed to a variable of (educational qualification, years of experience, place of kindergarten, and subordination kindergarten). The study concluded the following suggestions and conclusions, such as the necessity of providing the suitable means which educational films can be introduced through (TV, computer) and providing educational films with a high quality and presenting them for kindergarten children.